2012
DOI: 10.1016/j.wear.2011.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fastsim with variable coefficient of friction using twin disc experimental measurements

Abstract: ElsevierRovira Cardete, A.; Roda Buch, A.; Marshall, M. (2012). Application of Fastsim with variable coefficient of friction using twin disc experimental measurements. Wear. 274-275:109-126. doi:10.1016/j.wear.2011.08 AbstractIn the field of railway simulation, it is a general assumption to consider the coefficient of friction as a known and constant value. This hypothesis is clearly not correct as friction is a consequence of the operating conditions (an output, not an input) and many factors can cause fric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 33 publications
0
12
0
9
Order By: Relevance
“…Ideally full creep cures are needed for different third body materials. Recent work by Rovira et al [14] has shown, however, that the use of dry wear coefficients and not accounting for friction variation with slip can lead to very high errors in resulting contact forces and wear predictions. Work is ongoing to obtain a greater range of wear coefficients [15] and some can be seen in Figure 8 for dry, wet and grease lubricated conditions.…”
Section: Wear Measurements and Evaluationmentioning
confidence: 99%
“…Ideally full creep cures are needed for different third body materials. Recent work by Rovira et al [14] has shown, however, that the use of dry wear coefficients and not accounting for friction variation with slip can lead to very high errors in resulting contact forces and wear predictions. Work is ongoing to obtain a greater range of wear coefficients [15] and some can be seen in Figure 8 for dry, wet and grease lubricated conditions.…”
Section: Wear Measurements and Evaluationmentioning
confidence: 99%
“…En la presente Tesis se propone un método para identificar los parámetros que definen dichas funciones a partir de las mediciones experimentales de las curvas de tracción y que ha sido publicado en la referencia [91].…”
Section: A3 Función De Fricción Y Curva De Tracciónunclassified
“…Trabajos futuros basados en experimentación deberán definir parámetros de fricción y leyes de desgaste adecuadas para las distintas condiciones en las que se puede encontrar la interfase rueda-carril. Parte de este trabajo se ha publicado en la revista Wear [91].…”
Section: Conclusionesunclassified
See 2 more Smart Citations